Effects of intra-hippocampal injections of the NK2 receptor antagonist saredutant on the elevated plus maze, and the mouse defense test battery - Borelli, Karina Genaro; Defensor, Erwin B.; Blanchard, D. Caroline; Blanchard, Robert J.; Griebel, Guy (Neuroscience letters, 2010)
▶ Intra-ventral hippocampus of saredutant produced anxiolytic-like effects. ▶ Low dose of saredutant (10 pmol) reduced avoidance of the threat stimulus. ▶ Saredutant weakly modified defensive behaviors in mice confronted by a rat. ▶ Saredutant injected into the ventral hippocampus reduced the inhibitory defenses. ▶ Hippocampal tachykinergic mechanisms modulate aversive responses. Intracerebroventricular (i.c.v.) or intraperitoneal (IP) administration of saredutant (SR48968), an NK2 receptor antagonist, produces anxiolytic-like effects in rodents in a number of animal models of anxiety. NK2 binding sites are present in several limbic structures in rats, including the hippocampus, thalamus, septum and prefrontal cortex, suggesting involvement in the modulation of emotional processes. The current study investigated the behavioral effects of saredutant infused into the ventral hippocampus (VH), a structure associated with cognitive and emotional processes, to clarify the neural substrate underlying the anxiolytic-like effect of the compound. Saredutant (10, 100 or 500 pmol/0.2 μL) was injected bilaterally into the VH of male CD-1 mice tested in the elevated plus-maze and mouse defense test battery (MDTB). Results from the EPM showed that microinjections of 10 pmol/0.2 μL of saredutant increased entries and time spent in the open arms and enhanced end-arm exploration. In the MDTB, saredutant (500 pmol/0.2 μL) decreased vocalizations and increased escape attempts in mice confronted with a rat. Taken together, these results suggest that hippocampal tachykinin mechanisms are involved in the modulation of anxiety and defensive behaviors.